Pengaruh Terapi Komplementer Akupressur Terhadap Kejadian Mual Muntah Pasca Pembiusan Regional Blok (Spinal Anastesi ) Diruang Pulih Rumah Sakit Umum Imelda Pekerja Indonensia Medan - Satriani Hartalina Gultom; Candra Meriani Damanik; Yuni Shanti Ritonga; Syahrul Handoko Nainggolan; Ali Asman Harahap (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Postoperative nausea and vomiting is one of the common side effects of spinal anesthesia. Nausea and vomiting affect patient morbidity such as stress, discomfort, dehydration, prolonging treatment time and increasing treatment costs. This study aims to determine the effect of acupressure therapy on the incidence of nausea and vomiting after spinal anesthesia in the recovery room of the Imelda Buruh Indonesia General Hospital, Medan. This type of research is a quantitative study with a quasi-experimental research method. Data reports in the province of North Sumatra, there are 25,602 patients undergoing surgery. While at the Umim Buruh Indonesia Hospital, Medan, the data on surgical patients per January-March 2024 amounted to 666 patients, 250 patients were found to have spinal anesthesia. This study was conducted in February - June 2024 at the Imelda Buruh Indonesia General Hospital, Medan. A sample of 20 respondents was taken.: The results of the statistical test obtained an α value of 0.000 (α <0.05), thus it was concluded that there was an effect of acupressure therapy on the incidence of nausea and vomiting after spinal anesthesia at the Imelda Buruh Indonesia General Hospital, Medan. Based on the characteristics of respondents based on age, they were in the age range of 36-40 years, which was 55%, based on gender, the majority of respondents were women, which was 60%, respondents based on a history of smoking were 65%, the distribution of respondents with a history of nausea and vomiting was 55% and the majority of respondents with an incidence of nausea and vomiting was 60%. The recommendation for this study is that acupressure therapy can be applied in nursing practice so that patients are able to do it independently. For the Imelda Buruh Indonesia General Hospital, Medan, it is necessary to carry out a risk scoring of nausea and vomiting in patients before surgery to minimize the incidence of nausea and vomiting after surgery.